Pengaruh Persepsi Tentang Minimarket Terhadap Kondisi Sosial Ekonomi Pedagang di Pasar Tradisional Songgom - Andi Yulianto; Mukson Mukson (Universitas Peradaban, 2019)
The purpose of this study was to determine the effect of perceptions about mini markets on the socio-economic conditions of traders in traditional markets in Songgom. The research method used is a survey method with a quantitative approach. The population in this study was conducted on traders as many as 100. Hypothesis testing using product moment, coefficient of determination test, and alpha reliability test. Data collection techniques were carried out using questionnaires statements about mini markets and socio-economic conditions of traders in the traditional market in Songgom. Hypothesis testing uses multiple linear regression analysis through (F-test) and (t-test) to know the effect of independent variables on the dependent variable at a 95% confidence level (α = 0.05). The results showed that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected which meant that there was an influence between perceptions of mini markets on the socio-economic conditions of traders in Songgom traditional market.